A 9-Year-Old Girl Discovers That Her Mother Was Murdered. Issue 1 (February 2017) - Schonfeld, David J.; Shekunov, Julia; Jellinek, Michael; Stein, Martin T.
Abstract : CASE: Susan was a 9-year-old girl living with her mother; she had never met her father. Her mother returned one evening from her job as a cocktail waitress and Susan met her at the apartment door to let her know they had run out of cat food. Her mother said she would go and buy some the next morning because it was late and she was tired, but Susan insisted she go out that evening because the cat had not eaten all day. Her mother was fatally shot in the parking lot of the convenience store shortly thereafter; since there was no robbery involved, the police suspected it was someone that she knew. Susan's extended family had her move out of the apartment that evening and relocate to live with her aunt and uncle out-of-state. The transition happened quickly. Susan was unable to return to her apartment to pick up any additional belongings and never returned to say goodbye to her friends. The family decided she was too young to attend the funeral. Susan had trouble fitting in with her aunt and uncle's family; they had 2 children who were 8 and 6 years old, and Susan felt she was being treated like a baby. She resented having a bedtime (her mother allowed her to stay up as late as she wished), and she complained that the work at school was boring and her classmates were childish. When the family went to a festival in town, she left abruptly without telling them, which frightened Susan's aunt and uncle. They wanted to be supportive but felt that she needed more structure than her mother had provided her. Susan's aunt and uncle sought bereavement support for Susan from her pediatrician and parenting advice for themselves.